N-Type Thermoelectric Performance of Functionalized Carbon Nanotube-Filled Polymer Composites - Freeman, Dallas D.; Choi, Kyungwho; Yu, Choongho (PLOS ONE, 2012)
Carbon nanotubes (CNTs) were functionalized with polyethyleneimine (PEI) and made into composites with polyvinyl acetate (PVAc). CNTs were dispersed with different amounts of sodium dodecylbenzenesulfonate (SDBS) prior to the PEI functionalization. The resulting samples exhibit air-stable n-type characteristics with electrical conductivities as great as 1500 S/m and thermopowers as large as −100 µV/K. Electrical conductivity and thermopower were strongly affected by CNT dispersion, improving the properties with better dispersion with high concentrations of SDBS. This improvement is believed to be due to the increase in the number of tubes that are evenly coated with PEI in a better-dispersed sample. Increasing the amount of PEI relative to the other constituents positively affects thermopower but not conductivity. Air exposure reduces both thermopower and conductivity presumably due to oxygen doping (which makes CNTs p-type), but stable values were reached within seven days following sample fabrication.